FORMULASI DAN EVALUASI GEL HAND SANITIZER BERBASIS EKSTRAK DAUN API-API PUTIH (Avicennia alba Blume) - Urwatul Wutsqa, Yusfia; Aprisida Rahmawati, Ristia; Iqbal Halim, Muhamad (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Gel hand sanitizer is a gel-based hand cleaner used to cleanse or eliminate microorganisms on the hands. The white mangrove plant (Avicennia alba Blume) is a type of mangrove widely distributed throughout Indonesia and is abundant in nature. White mangrove has also been reported to be non-cytotoxic and can be used as a medicinal ingredient. The active compounds responsible for antibacterial properties in white mangrove plants include flavonoids, saponins, and tannins. Hand sanitizer can be made from the leaves of the white mangrove plant. This study aims to formulate a gel hand sanitizer from white mangrove leaf extract and evaluate the gel hand sanitizer formulation using concentrations of 30%, 20%, and 10%. The analysis method used in this research is descriptive. The study results show that the extract can be formulated into a gel preparation, and some formulations meet the evaluation criteria. The formula that meets all the evaluation criteria is F1, while F2 meets the criteria for organoleptic tests, pH tests, viscosity tests, adhesion tests, and homogeneity tests but does not meet the criteria for the spreadability test. On the other hand, F3 meets the criteria for organoleptic tests, pH tests, viscosity tests, and adhesion tests but does not meet the criteria for homogeneity and spreadability tests.